Passenger car handling model validation using LMS-DADS - Mohd. Samin, Pakharuddin; Tang, Siew Eng; Hudha, Khisbullah (2006)
This paper presents the modeling and validation of a multibody passenger car model to evaluate the handling performance. LMSDADS generated the multibody passenger car model with PROTON WAJA as the benchmark. Several transient handling performance test had been performed, included double-lane change test, J-turn test and Slalom test at constant speed. An openloop study is performed to evaluate the handling performance which the model responded to the steering input given. Comparisons of the experiment result and model simulation with steering wheel imposed motion are made. Some of the quantities illustrated include steering wheel input, lateral acceleration and yaw rate. Predictions of the model’s responses agree with the actual measured vehicle’s responses within some specified level of accuracy using qualitative validation.